2018
DOI: 10.1371/journal.pone.0191514
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic drugs can amplify spatial heterogeneities in the electrical restitution in perfused guinea-pig heart: An evidence from assessments of monophasic action potential durations and JT intervals

Abstract: Non-uniform shortening of the action potential duration (APD90) in different myocardial regions upon heart rate acceleration can set abnormal repolarization gradients and promote arrhythmia. This study examined whether spatial heterogeneities in APD90 restitution can be amplified by drugs with clinically proved proarrhythmic potential (dofetilide, quinidine, procainamide, and flecainide) and, if so, whether these effects can translate to the appropriate changes of the ECG metrics of ventricular repolarization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In these dogs, the APD prolongation was larger in the left ventricle than in the right ventricle (647). The opposite was observed in guinea pigs, i.e., the APDprolonging drugs dofetilide and quinidine lengthened APD more in the right ventricle (651). These findings highlight important differences among species in their responses to drugs with repolarization-prolonging effects.…”
Section: Ventricular Action Potentials: Transmural and Regional Differencesmentioning
confidence: 71%
“…In these dogs, the APD prolongation was larger in the left ventricle than in the right ventricle (647). The opposite was observed in guinea pigs, i.e., the APDprolonging drugs dofetilide and quinidine lengthened APD more in the right ventricle (651). These findings highlight important differences among species in their responses to drugs with repolarization-prolonging effects.…”
Section: Ventricular Action Potentials: Transmural and Regional Differencesmentioning
confidence: 71%
“…K ϩ CHANNEL ISOFORMS REGULATE HUMAN ATRIAL ARRHYTHMOGENESIS current and associated details of atrial refractoriness (18,48,88,125) or on whether the K ϩ channels that underlie I to are predominantly Kv1.4 or Kv4.3 (cf. 85,121).…”
Section: H537mentioning
confidence: 99%
“…If so, it is important to recognize that when Kv1.4 is the predominant drug "target," it can confer new electrophysiological properties to the atrial substrate (2,10,23,48,63,71,80,85). Moreover, the spatial heterogeneity of the electrophysiological properties in mammalian atria (right vs. left atrium, right atrium vs. atrial septum) will need to be accounted for (36,39,86) since it is known that any significant differences in spatial localized APD within the atrial syncytium can influence arrhythmogenesis (88,96,114).…”
Section: H537mentioning
confidence: 99%
“…Epicardial APD heterogeneity was also more prominent during slower versus faster pacing rates. Prior studies have reported regional heterogeneity between the left versus right ventricle 75 using isolated ventricular cardiomyocytes, and/or base versus apex 46 in intact heart preparations from young guinea pigs. Although, in our study, regional heterogeneity was largely absent in adult animals ( Figure 5C , Figure 7D-E ).…”
Section: Discussionmentioning
confidence: 99%